Incidence, Risk Factors and Impact on Long-Term Outcome of Postoperative Delirium After Transcatheter Aortic Valve Replacement - Mauri, Victor; Reuter, Kevin; Körber, Maria I.; Wienemann, Hendrik; Lee, Samuel; Eghbalzadeh, Kaveh; Kuhn, Elmar; Baldus, Stephan; Kelm, Malte; Nickenig, Georg; Veulemans, Verena; Jansen, Felix; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The aim of the present study was to analyze incidence, risk factors, and association with long-term outcome of postoperative delirium (POD) after transcatheter aortic valve replacement (TAVR). Methods: Six hundred and sixty one consecutive patients undergoing TAVR were prospectively enrolled from January 2016 to December 2017. POD was assessed regularly during ICU-stay using the CAM-ICU test. Results: The incidence of POD was 10.0% (n = 66). Patients developing POD were predominantly male (65%), had higher EuroSCORE II (5.4% vs. 3.9%; P = 0.041) and were more often considered frail (70% vs. 26%; P < 0.001). POD was associated with more peri-procedural complications including vascular complications (19.7 vs. 9.4; P = 0.017), bleeding (12.1 vs. 5.4%; P = 0.0495); stroke (4.5 vs. 0.7%; P = 0.025), respiratory failure requiring ventilation (16.7% vs. 1.8%; P < 0.001), and pneumonia (34.8% vs. 7.1%; P < 0.001). Consequently, patients with POD had significantly longer ICU- (7.9 vs. 3.2 days P < 0.001) and hospital-stay (14.9 vs. 9.0 days; P < 0.001), and higher in-hospital mortality (6.1 vs. 2.1%; P = 0.017). Logistic regression analysis identified male sex (odds ratio (OR) 2.2 [95% confidence interval (CI) 1.2–4.0); P = 0.012], atrial fibrillation [OR 3.0 (CI 1.6–5.6); P < 0.001], frailty [OR 4.3 (CI 2.4–7.9); P < 0.001], pneumonia [OR 4.4 (CI 2.3–8.7); P < 0.001], stroke [OR 7.0 (CI 1.2–41.6); P = 0.031], vascular complication [OR 2.9 (CI 1.3–6.3); P = 0.007], and general anesthesia [OR 2.0 (CI 1.0–3.7); P = 0.039] as independent predictors of POD. On Cox proportional hazard analysis POD emerged as a significant predictor of 2-year mortality [HR 1.89 (CI 1.06–3.36); P = 0.030]. Conclusion: POD is a frequent finding after TAVR and is significantly associated with reduced 2-year survival. Predictors of delirium include not only peri-procedural parameters like stroke, pneumonia, vascular complications and general anesthesia but also baseline characteristics as male sex, atrial fibrillation and frailty.